ANALISIS KOMUNIKASI GLOBAL MELALUI FILM DALAM DISKURSUS YANG MENYUDUTKAN ISLAM - Laode Muhamad Fathun (Dauliyah Journal of Islamic and International Affairs, 2018)
Globalization brings sovereignty of the country as indefinitely. Glo-balization makes global communication increasingly limited. Communica-tion through diplomacy is the way in mengespresikan kepentinganya any State against another State. Due to the influence of technology in the glo-balization phenomenon makes the instrument of diplomacy was changed as well as the jumlaah actors. Conventional diplomacy that uses Ministry of Foreign Affairs as a single actor has shifted to the public role in the for-mation of international opinion. Reatif diplomatic instruments through the film is one way to India through the representatives of film directors in the form fictional story to make a change on the discourse discourse meaning of Islam as a terrorist religion. The discourse of meaning making psychological blow for followers of the Muslim identity of the adherents of identity that is considered by some countries call it the United States as an actor fundamentalism. Through instrument Indian Bollywood films try to shape public opinion, especially the people of the United States that fact does Islam not as bad as perception shown in US foreign policy.